The Biological Profile of the Less Lipophilic and Synthetically More Accessible Bryostatin 7 Closely Resembles That of Bryostatin 1 - Kedei, Noemi (2013)
[Image: see text] The bryostatins are a group of twenty macrolides isolated by Pettit and coworkers from the marine organism Bugula neritina. Bryostatin 1, the flagship member of the family, has been the subject of intense chemical and biological investigations due to its remarkably diverse biological activities, including promising indications as therapy for cancer, Alzheimer’s disease, and HIV. Other bryostatins, however, have attracted far less attention, most probably due to their relatively low natural abundance and associated scarcity of supply. Among all macrolides in this family, bryostatin 7 is biologically the most potent PKC (protein kinase C) ligand (in terms of binding affinity) and also the first bryostatin to be synthesized in the laboratory. Nonetheless, almost no biological studies have been carried out on this agent. We describe herein the total synthesis of bryostatin 7 based on our pyran annulation technology, which allows for the first detailed biological characterizations of bryostatin 7 with side-by-side comparisons to bryostatin 1. The results suggest that the more easily synthesized and less lipophilic bryostatin 7 may be an effective surrogate for bryostatin 1.